Pendidikan Agama Kristen Berpola Pedagogik Transformatif Pada Era Revolusi Industri 4.0 Menurut Matius 11:28-30 - Sensius Amon Karlau; Ivo Sastri Rukua; Jeffrit Kalprianus Ismail (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The urgency of this study aims to explain the actualization of Christian religious education which currently seems not to be going in rhythm with various expectations. This condition occurs because of the rapid demands of science and information networks development in the era of the industrial revolution 4.0 intertwined with waves of disruption. It is ironic because, in practice, some teachers still use conventional patterns. This of course is tedious and burdensome. The author uses a qualitative method with a literature approach and concludes that the praxis of Christian religious education is intertwined with a transformative call in the semantic meaning of Matthew 11:28-30. Therefore, the actualization of Christian religious education must be passionate, provide relief, be interactive, and dialogical, and lead to an invitation to learn continuously by educators to students gently and pleasantly as the Lord Jesus did.